A Case of Paraneoplastic Encephalitis Arising from Concurrent Thymoma and Stage I Adenocarcinoma of the Lung (Archives of Clinical and Medical Case Reports, 2021)
Paraneoplastic Encephalitis (PE) is a rare syndrome that arises as a tumor-induced autoimmune response which can cause focal or diffuse nervous system dysfunction. Patients commonly present with a variety of neurologic symptoms, depending on the inflammatory distribution, and possibly with other symptoms stemming from the primary cancer. We herein present a never-smoker patient who presented with dysarthria, dysphagia and cognitive decline, and required numerous diagnostic examinations, sometimes invasive ones, for correct staging and diagnosing of the primary malignancy. Of note, despite the lack of clear evidence suggesting metastatic disease based on neuroimaging, a brain biopsy was nonetheless performed for diagnostic purposes. The patient was diagnosed with paraneoplastic encephalitis stemming from two independent primary cancers: an early stage lung adenocarcinoma and a concomitant type B3 thymoma. In addition to displaying a unique case of a paraneoplastic disorder associated with two simultaneous cancers, this report highlights the diagnostic challenge of paraneoplastic encephalitis and discusses important imaging findings with the goal of preventing invasive and evitable brain biopsies in similar future cases.